Hubungan Perilaku dan Lingkungan Dengan Kejadian Demam Berdarah Dengue di Wilayah Kerja Puskesmas Tigo Baleh Kecamatan Aur Birugo Tigo Baleh Kota Bukittinggi Tahun 2014 - Sulistiawan, Andika; Rina, Rina (LPPM Universitas Prima Nusantara Bukittinggi, 2015)
Dengue hemorrhagic fever (DHF) is a health problem with an increasing number of cases is equal to 65.57 per 100 thousand inhabitants. Based on data from the health department of Bukittinggi in 2011-2013 the number of dengue cases in the region Puskesmas Tigo Baleh In 2011 as many as 20 cases, 35 cases were in 2012, in 2013 a total of 39 cases. this type of research is an analytic survey with case-control study design and size of the study respondents were 78 respondents with totaly sampling technique. The data was collected using a questionnaire with interview techniques. This research uses the chi-square test with 95% degree of confidence (É‘ = 0.05). The results showed no significant relationship between knowledge of the incidence of DHF (p = 0.000, OR 59,500), there was no significant relationship between the attitude of the incidence of DHF (p = 0.074, OR 2.066), a significant relationship between the incidence of dengue measures (p = 0.030 , OR 4.500), and no significant relationship between the environment and the incidence of DHF (p = 1.000 OR 2.054). Expected, government and health centers can improve public knowledge and action better through counseling with a more effective method.